Perencanaan Pendidikan di MAS Al-Washliyah Kecamatan Medan Area Kota Medan - Mesiono; Rina Hidayah Tambusai; Abdul Halim; Rabbirham (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study examines educational planning at MAS Al-Washliyah, with a particular focus on the implementation of educational plans, parental participation, and curriculum challenges. The research aims to evaluate the implementation of educational plans, analyze the role of parents, and investigate curriculum challenges. The findings reveal that the implementation of educational plans at MAS Al-Washliyah has been successful in improving student learning outcomes through a diverse and relevant curriculum and close collaboration between the school and parents. Despite these successes, the school faces challenges in adapting the curriculum to the rapid pace of developments in science and technology. Recommendations for further research include embracing criticism and feedback for continuous improvement. The research employed a qualitative approach, utilizing data collection techniques such as interviews, observations, and document analysis. Data analysis was conducted using triangulation techniques.